Presence Relates to Distinct Outcomes in Two Virtual Environments Employing Different Learning Modalities - Persky, Susan (2009)
Presence in virtual learning environments (VLEs) has been associated with a number of outcome factors related to a user’s ability and motivation to learn. The extant but relatively small body of research suggests that a high level of presence is related to better performance on learning outcomes in VLEs. Different configurations of form and content variables such as those associated with active (self-driven, interactive activities) versus didactic (reading or lecture) learning may, however, influence how presence operates and on what content it operates. We compared the influence of presence between two types of immersive VLEs (i.e., active versus didactic techniques) on comprehension and engagement-related outcomes. The findings revealed that the active VLE promoted greater presence. Although we found no relationship between presence and learning comprehension outcomes for either virtual environment, presence was related to information engagement variables in the didactic immersive VLE but not the active environment. Results demonstrate that presence is not uniformly elicited or effective across immersive VLEs. Educational delivery mode and environment complexity may influence the impact of presence on engagement.